Bioactive glass and high‐intensity lasers as a promising treatment for dentin hypersensitivity: An in vitro study. Issue 3 (5th August 2019) - Lee, Ester M. R.; Borges, Roger; Marchi, Juliana; de Paula Eduardo, Carlos; Marques, Márcia M.
Abstract: This in vitro study aimed to analyze the physical and chemical characteristics of the hypersensitive human dentin‐like surface after application of a bioactive glass (BG) paste (BG/Ac) irradiated or not with high‐power lasers. Dentin specimens were treated with 17% Ethylenediamine tetraacetic acid (EDTA) solution to mimic a hypersensitive dentin and then submitted to neodymium: yttrium–aluminum–garnet (Nd:YAG) laser or CO2 laser irradiation prior and after application of BG/Ac. Characterizations were performed by using X‐ray diffraction, Fourier transformed infrared spectroscopy, scanning electron microscopy, and energy dispersive X‐ray spectroscopy. The results suggested that application of BG/Ac by itself caused some obstructions of dentinal tubules. Nd:YAG laser irradiation reduced the opening of the dentinal tubules with no changes in the collagen structure. CO2 laser irradiation caused dentin melting and resolidification along with cracks and chemical changes in collagen fibers. However, when BG/Ac paste was irradiated with lasers, a sequence of surface reactions between glass and dentin interface led to the formation of an amorphous hydroxyapatite layer, similar to that of an inorganic component of the normal dentin. Moreover, BG/Ac was able to prevent the formation of cracks and degradation of collagen fibers caused by CO2 irradiation. Overall, this study supports that application of BG/Ac paste irradiated by high‐power laser could represent an effective and long‐lasting therapeutic approach for dentin hypersensitivity.